Assessment of Lateral Rotation Percentage and Rotational Deformity of the Elbow in Type 3 Supracondylar Humerus Fractures: A Biomechanical Study. Issue 8 (7th September 2021) - Berdis, Galen; Hooper, Matthew; Talwalkar, Vishwas; Walker, Janet; Muchow, Ryan; Riley, Scott; Iwinski, Henry J.; Prusick, Vincent
Abstract : Background: Supracondylar humerus (SCH) fractures are the most common elbow fractures in children. Historically, displaced (Gartland type 3) SCH fractures have been treated with closed reduction and percutaneous pinning. Fluoroscopic imaging is used intraoperatively in order to assess adequate reduction of the fracture fragments before pinning. On lateral fluoroscopic and radiographic images, a lateral rotation percentage (LRP) can be estimated in order to assess rotational deformity. The purpose of this study was to determine the true rotational deformity of distal humerus fracture fragments in SCH fractures based upon the LRP using a clinically relevant laterally based pinning technique. Methods: In this study, a sawbones model was used to examine the correlation between calculated LRP and the true degree of rotational deformity with 3 of the most common extension-type SCH fracture types (low transverse, high transverse, and lateral oblique). Because fracture stability was not the focus of this study, a single pin was used to hold the construct and allow for fragment rotation along a fixed axis. In this study, 2 of the authors independently measured rotational deformity and compared this with LRP on fluoroscopic lateral imaging of a sawbones model at 0 to 45 degrees of rotational deformity. Results: The LRP of all 3 patterns demonstrated a near linear increase from 0 to 45 degrees with maximum LRP measured at 45 degrees for each of the 3 patterns. Univariate linear regression demonstrated an increase in LRP for the low transverse pattern of 2.02% for every degree of rotation deformity ( R 2 =0.97), 2.29% for the lateral oblique pattern ( R 2 =0.986), and 1.17% for the high transverse pattern ( R 2 =0.971). Maximum LRP was measured at 45 degrees for all 3 patterns with a mean of 53.5% for the high transverse pattern, 93.5% for the low transverse pattern, and 111.2% for the lateral oblique pattern. A higher LRP was measured with increasing degrees of rotational displacement in the low transverse and lateral oblique patterns for all degrees of rotational deformity compared to the high transverse pattern. Conclusion: There is a near linear correlation between the degree of malrotation and the LRP with more superior metaphyseal fracture patterns demonstrating a lower LRP than inferior fracture patterns. Clinical Relevance: Using our data one can estimate the degree of malrotation based on the LRP on radiographs in the clinical setting. Level of Evidence: Not applicable (basic-science article).